Using loop-primer mediated PCR to enhance the detection of poorly preserved DNA - Xiang, Hai; Wang, Zhi; Yang, Liu; Zhang, Xing; Zhao, Xingbo (Frontiers in Genetics, 2022)
Ancient DNA is vitally important in evolutionary research, and obtaining authentic ancient DNA sequences is critical for a proper analysis. However, it is difficult to acquire amplicons accurately and efficiently from ancient DNA templates using current techniques. Here, we established a loop-primer-mediated amplification method (L-PCR) to obtain target ancient DNA sequences with high accuracy and efficiency. The method was tested using 66 ancient samples (including 27 pig bones or teeth and 39 chicken bones) and serially diluted modern animal DNA templates. Compared to nested PCR, L-PCR was proven to be more efficient and accurate and could obtain more amplicons from both ancient pig samples and chicken bones and detect as low as 10−3 ng/μl modern pig template DNA. The efficiency was at least 100-fold that of the nested PCR. The results suggest that L-PCR is advantageous for obtaining authentic DNA sequences from poorly preserved or recalcitrant ancient specimens.